Substantial observer variability in the differentiation between primary intracerebral hemorrhage and hemorrhagic transformation of infarction on CT brain imaging. - Lovelock, C; Anslow, P; Molyneux, A; Byrne, J; Kuker, W; Pretorius, P; Coull, A; Rothwell, P (2009)
BACKGROUND AND PURPOSE: CT remains the most commonly used imaging technique in acute stroke but is often delayed after minor stroke. Interobserver reliability in distinguishing hemorrhagic transformation of infarction from intracerebral hemorrhage may depend on delays to CT but has not been reported previously despite the clinical importance of this distinction. METHODS: Initial CT scans with intraparenchymal hematoma from the first 1000 patients with stroke in the Oxford Vascular Study were independently categorized as intracerebral hemorrhage or hemorrhagic transformation of infarction by 5 neuroradiologists, both blinded and unblinded to clinical history. Thirty scans were reviewed twice. Agreement was quantified by the kappa statistic. RESULTS: Seventy-eight scans showed intraparenchymal hematoma. Blinded pairwise interrater agreements for a diagnosis of intracerebral hemorrhage ranged from kappa=0.15 to 0.48 with poor overall agreement (kappa=0.35; 95% CI, 0.15 to 0.54) even after unblinding (kappa=0.41; 0.21 to 0.60). Blinded intrarater agreements ranged from kappa=0.21 to 0.92. Lack of consensus after unblinding was greatest in patients scanned >or=24 hours after stroke onset (67% versus 25%, P=0.001) and in minor stroke (National Institutes of Health Stroke Scale <or=5: 29%,="" 56%="" 75%="" disagreement="" in="" of="" p="0.04)" patients="" scanned="" versus="" with="">or=24 hours after minor stroke and in 48% of all 30-day stroke survivors in whom reliable diagnosis would be expected to influence long-term management. CONCLUSIONS: Reliability of diagnosis of intraparenchymal hematoma on CT brain scan in minor stroke is poor, particularly if scanning is delayed. Immediate brain imaging is justified in patients with minor stroke.</or=5:>